DNA‐Compatible Click Reaction Employing In Situ Generated Azides from Boronic Acids. Issue 5 (6th May 2021) - An, Yulong; Yan, Hao; Dong, Zhenzhen; Satz, Alexander L.
Abstract: An efficient method for the synthesis of DNA‐conjugated 1, 2, 3‐triazoles is copper (II) [Cu(II)‐β‐cyclodextrin]‐mediated Huisgen cycloaddition ("click reaction") of DNA‐conjugated alkynes with azides. However, a diverse array of building blocks is required to produce useful DNA encoded libraries, and the commercial availability of azides is limited. The method described herein generates azides in situ from aryl borates and TMSN3, which then further react with DNA‐conjugated terminal alkynes. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Conjugation of PEG linker to DNA headpiece Basic Protocol 2 : DNA conjugated terminal alkyne preparation Basic Protocol 3 : DNA compatible one‐pot click reaction Basic Protocol 4 : LCMS monitoring